Burnout : the secret to unlocking the stress cycle - Nagoski, Emily; Nagoski, Amelia (Ballantine Books, 2020)
"Burnout. Many women in America have experienced it. What's expected of women and what it's really like to be a woman in today's world are two very different things--and women exhaust themselves trying to close the gap between them. How can you 'love your body' when every magazine cover has ten diet tips for becoming 'your best self'? How do you 'lean in' at work when you're already operating at 110 percent and aren't recognized for it? How can you live happily and healthily in a sexist world that is constantly telling you you're too fat, too needy, too noisy, and too selfish? Sisters Emily Nagoski, PhD, and Amelia Nagoski, DMA, are here to help end the cycle of feeling overwhelmed and exhausted. Instead of asking us to ignore the very real obstacles and societal pressures that stand between women and well-being, they explain with compassion and optimism what we're up against--and show us how to fight back."--Amazon.com